2007
DOI: 10.1590/s0103-90162007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Short-term assessment of bt maize on non-target arthropods in Brazil

Abstract: ABSTRACT:Although not yet available for cultivation in Brazil, the effect of Bt maize hybrids on natural enemies and soil dwelling arthropods should be assessed prior to its release to growers. Trials were carried out during one growing season in two different locations with the genetically modified maize hybrids 7590-Bt11 and Avant-ICP4, comparing with their respective non-Bt isogenic hybrids. Arthropods were evaluated through direct observation on plants and pitfall traps. In general, no differences were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
3
9
0
Order By: Relevance
“…Based on the average number of earwigs collected from the corn plants, observed that the abundance of D. luteipes was similar for all treatments in four seasons, suggesting that MON810 does not affected the dynamics of the predator in the short term (Figure 3). No effect of Bt corn expressing Cry1Ab on D. luteipes population was also reported under fi eld conditions in Brazil by FERNANDES et al (2007). It is possible that the populations of D. luteipes found suffi cient amounts of available food in the MON810 corn throughout the crop cycle (i.e., eggs, neonate and small larvae of S. frugiperda).…”
Section: Resultsmentioning
confidence: 98%
“…Based on the average number of earwigs collected from the corn plants, observed that the abundance of D. luteipes was similar for all treatments in four seasons, suggesting that MON810 does not affected the dynamics of the predator in the short term (Figure 3). No effect of Bt corn expressing Cry1Ab on D. luteipes population was also reported under fi eld conditions in Brazil by FERNANDES et al (2007). It is possible that the populations of D. luteipes found suffi cient amounts of available food in the MON810 corn throughout the crop cycle (i.e., eggs, neonate and small larvae of S. frugiperda).…”
Section: Resultsmentioning
confidence: 98%
“…In one study, the rates of parasitism of O. nubilalis eggs and egg masses were low (~2-6%) in both Bt and conventional maize fields, and did not differ significantly between the fields (Orr and Landis 1997). In the second study, the rates of parasitism of Helicoverpa zea (Boddie) eggs were consistentlỹ 30% in Bt and conventional maize fields, and did not differ significantly between the fields (Fernandes et al 2007). However, as in the case of cotton, both studies employed small experimental plots, were not replicated in time, and plots were minimally replicated (n = 3), so their results should be considered inconclusive.…”
Section: Gm Crop-egg Parasitoid Interactions Under a Loupe: Field Stumentioning
confidence: 92%
“…Most studies in the USA, Europe and China suggest Bt maize has little if any impact on predators and parasitoids and, when compared with maize treated with chemical insecticides, Bt maize often results in increased biodiversity (Bourguet et al, 2002;Candolfi et al, 2003;Dutton et al, 2003;Bhatti et al, 2005a, b;Daly and Buntin, 2005;de la Poza et al, 2005;Dively, 2005;Pilcher et al, 2005;Romeis et al, 2006;Fernandes et al, 2007;Marvier et al, 2007;Wang et al, 2007; for general reviews see O'Callaghan et al, 2005;Romeis et al, 2008;chapter 4). Although maize is not a major source of pollen for honey bees, Apis mellifera (Hymenoptera: Apidae), the US Environmental Protection Agency (USEPA) requires information on possible effects of Bt maize on honey bees.…”
Section: Effects On Non-target Organismsmentioning
confidence: 99%